Supply chain management at the base of the pyramid. Issue 5 (12th June 2019) - Tate, Wendy L.; Bals, Lydia; Marshall, Donna
Abstract : Purpose: The purpose of this paper is to compile a set of articles tackling supply chain issues in BOP contexts that address both demand and supply. Solutions are needed for global sustainability problems from medical aid and food availability to the ability to participate in supply chains for the global poor. Design/methodology/approach: The accepted articles in the special issue used a range of qualitative and quantitative methodologies to answer research questions in a variety of base of the pyramid (BOP) contexts. These approaches and results distinguish between demand (BOP market) and supply, or base of the chain (BOC), perspectives. Findings: The findings in the eight accepted marticles are interesting and applicable across different BOP contexts. Compilation of the articles into the special issue and the accompanying editorial led to a comprehensive future research agenda that addresses demand-side issues by investigating the customers in BOP markets, and supply-side issues focusing on the suppliers and intermediaries (BOC) who supply BOP markets. Future research ideas include a focus on supply chain design issues situated at the intersection of the demand (BOP) and the supply (BOC) concerns that address the needs of the world's poorest populations. Research limitations/implications: All of the selected articleshave societal implications related to addressing the needs of BOP populations. Many of these articles also have economic and environmental implications, the other two pillars of the triple bottom line. The detailed future research agenda developed in this editorial presents implications for researchers working in emerging and BOP communities to push research forward and further develop the foundational literature in the BOP context. Practical implications: From a practical standpoint, each of the eight articles presents ideas for businesses that help address the needs of the global poor while enhancing global sustainability performance. The editorial summarizes these implications and provides new directions and examples of success in the BOP context. Managers are provided with techniques to address the supply and demand side of these growing markets. Originality/value: The overall conceptual framework and positioning of the final papers into the BOP market, BOC suppliers and a combination of the two is novel and helps provide guidance to both scholars and managers.